Biological Disease-Modifying Antirheumatic Drugs Decrease Uric Acid Levels in the Sera of Patients with Psoriatic Arthritis - Dijana Perković; Marin Petrić; Maja Maleš; Ivana Erceg Maleš; Mislav Radić (Current Issues in Molecular Biology)
Objectives: There are many explanations for increased levels of serum uric acid (SUA) in patients with psoriatic arthritis (PsA), but correlation with different treatment options in PsA is not well elucidated. Our aim was to determine the effects of biological disease-modifying antirheumatic drugs (bDMARDs) on SUA levels in patients with PsA. Materials and methods: We analyzed the data of PsA patients treated with different bDMARDs from January 2007 to June 2021. Patients treated with interleukin-17 (IL-17) inhibitors (secukinumab and ixekizumab) and tumor necrosis factor α (TNFα) inhibitors (golimumab, infliximab, adalimumab, certolizumab pegol, and etanercept) were included. Results: A total of 87 patients were included. The SUA levels decreased in 60 (69%) patients after a 3–6-month-long follow-up, and in 25 (28.7%), we noticed an increase. The average decrease in SUA levels was 9.4 ± 49.5 µmol/L (p = 0.039); for TNFα patients, it was 7.3 ± 59.8 µmol/L (p = 0.386), and for IL-17 patients, it was 12.6 ± 28.4 µmol/L (p = 0.013). The levels of SUA decreased in 81.8% of patients treated with infliximab, as well as in 76% of those treated with secukinumab and in 72.7% of those treated with etanercept. The largest average decrease in SUA levels was recorded in the group treated with golimumab (23 µmol/L). Conclusions: A significant decrease in SUA levels was noticed, especially in patients treated with IL-17 inhibitors. Further studies should identify which bDMARD is the most potent in the lowering of SUA levels. bDMARDs were efficient in PsA disease activity.